1997
DOI: 10.1111/j.1365-2133.1997.tb03785.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photochemotherapy induces apoptosis of infiltrating lymphoid cells in patients with mycosis fungoides in early stages. A quantitative histological study

Abstract: Extracorporeal photochemotherapy (ExP) is a well-tolerated new form of chemoimmunotherapy, which is considered to be effective for cutaneous T-cell lymphoma (CTCL) and the treatment of choice for Sézary syndrome. Improvements have also been seen in patients with non-erythrodermic mycosis fungoides (MF) in the early stages, even when tumour cells are not detectable in the peripheral blood. In this study, we used ExP as a monotherapy in seven patients who had early stage (Ib) MF, and who were no longer responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 38 publications
1
35
0
1
Order By: Relevance
“…The lymphocytes are then irradiated with UVA and subsequently transferred back to the patient. The mode of action is unclear, but it is suggested that 8‐methoxypsoralen (8‐MOP) forms covalent photoadducts with the nuclear DNA, thereby affecting the antigenicity and immunogenicity of the neoplastic cells which have been exposed to UVA 44 . These antigenetically altered lymphocytes are then felt to stimulate the host's immune system, mediated by CD8+ lymphocytes that target the malignant clone 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The lymphocytes are then irradiated with UVA and subsequently transferred back to the patient. The mode of action is unclear, but it is suggested that 8‐methoxypsoralen (8‐MOP) forms covalent photoadducts with the nuclear DNA, thereby affecting the antigenicity and immunogenicity of the neoplastic cells which have been exposed to UVA 44 . These antigenetically altered lymphocytes are then felt to stimulate the host's immune system, mediated by CD8+ lymphocytes that target the malignant clone 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Pheresis and treatment of patient leukocytes with a photo-sensitizing compound (ex, methoxypsoralen) followed by UVA exposure to delete reactive cells and re-infusion has shown promise in some HCT transplants [224][225][226]. The mechanisms involved in the ECP therapy are not understood but may include apoptosis, modulation of CD8, NK as well as antigen presenting cell activity [227][228][229][230][231]. The potential to selectively delete reactive cells in situ, for example, in the skin during cutaneous GVHD by exposure to some level of UVA may also show promise [232,233].…”
Section: Regulation Of Gvhd: Stagementioning
confidence: 99%
“…B. die Translokation von Phosphatidylseringruppen von der inneren zur äuûeren Zellmembranseite, Veränderungen der Chromatintextur mit Hilfe von DNA-bindenden Farbstoffen und eine intrazelluläre Verringerung des pHWertes am Tag 2 der ECP-Behandlung, konnte in dieser Untersuchung nachgewiesen werden. Auch eine Reihe von weiteren Untersuchungen konnten die ECP-Effekte bestätigen; ApoptoseMarker steigen nach 24 Stunden und nach 48 Stunden signifikant an und auch in Hautläsionen von CTCL-Patienten zeigt sich Apoptose von Lymphozyten [26]. Osella-Abate u. Mitarb.…”
Section: Ecp-induzierte Apoptoseunclassified